COMPARASION OF BASAL METABOLIC RATE MEASURED AND PREDICTED FROM WHEELCHAIR BASKETBALL PLAYERS (Fiep Bulletin - online, 2011)
BACKGROUND: To meet the energy demands is essential in maintaining lean body mass, immune system and physical performance and dietary recommendations for athletes is based on daily needs and the specificities of the sport. In disabled athlete, the energy requirement can be altered by changes in body composition caused by chronic use of a wheelchair and by the characteristics of disability. The basal metabolic rate (BMR) is the most important quantitative component of energy expenditure and how the World Health Organization (WHO) suggests that the same components are expressed as multiples of BMR, it must be estimated as close to reality as possible to appropriate prescription of physical activity and energy. OBJECTIVE: To determine the BMR of adapted basketball players by indirect calorimetry and compare your result with the prediction equation recommended by WHO (FAO/WHO/UNU, 1985) and Harris and Benedict (1919). METHODS: There was evaluated15 adapted basketball players, male, initially it was measured the body mass (kg) and height (m). Body mass composition was performed by the method “Dual-energy X-ray absorptiometry” (DXA). The BMR was measured by indirect calorimetry (BMRm) with a protocol validated by Wahrlich et al (2006) and compared with values generated by the prediction equations (BMRp). The paired t-Student test was used to determine the difference between BMRm and BMRp. To describe the correlation between TMB, age, body mass and body composition, it was used the linear correlation coefficient of Pearson. RESULTS: The average was BMRm 1375.19 kcal (±376.48 kcal), significantly lower than the BMRp, and the equation of the FAO / WHO / UNU was the most overestimated BMR (26.6%). There was a strong correlation between BMRp and those with body mass and lean body mass. CONCLUSÃO: The BMRp not reliably predicts the BMR of basketball players adapted, when compared with BMRm.
Keywords: basal metabolic rate; basketball adapted; physically handicapped